Studi Social Climber Gen-Z dan Perilaku Ekonominya - Bado, Basri; Tahir, Thamrin; Supatminingsih, Tuti (Journal of Economic Education and Entrepreneurship Studies, 2023)
This research explains the phenomenon of Gen-Z social climber behavior towards the development of coffee shops in Palopo city. This research aims to find out the meaning of coffee shop for Gen-Z life, Coffee Shop as a Marker of Gen-Z Social Identity, and Efforts to Fulfill Gen-Z Lifestyle Needs towards Social Climber Formation Behavior. The type of research used is a qualitative data processing method through a phenomenological approach and data collection is carried out with 3 methods, namely observation, interviews, and documentation with 5 informants. Data collection techniques in this study were carried out using purposive sampling techniques. Data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. From the results of the research, it can be obtained a general picture that Gen-Z in Palopo city visits and makes coffee shops as secondhome with the intention of showing their lifestyle as a symbolic message to someone who sees it, because other people's judgments are seen from what is shown. The lifestyle of hanging out in coffee shops displayed by them is solely to please or satisfy themselves for the recognition of their social class identity. The efforts they make to fulfill this lifestyle include working and saving.